Modificación de ambientes lóticos para la extracción de carbón a cielo abierto: Efectos sobre la biota y recomendaciones - Roa-Fuentes, Camilo Andrés; Pérez-Mayorga, María Angélica [UNESP] (Universidad Nacional de Colombia, 2018)
Open coal mining will cause a series of modifications to different lotic environments in Colombia. In this paper we analyzed the case of an open pit coal mine located in the Department of La Guajira, Colombia, focusing on the state of knowledge of the ichthyofauna, the potential effects of modifications on aquatic communities and the effectiveness of restoration/compensation measures. To assess the state of knowledge of the ichthyofauna, we reviewed relevant literature and used the ICE species richness estimator. To identify the potential effects of the modifications on aquatic biota and the effectiveness of the restoration/compensation measures, we carried out a literature review. We found that about 42% of the fish species in the Ranchería river basin and the mining concession area are still unknown. Furthermore, related studies indicate that the modifications will negatively affect the physical characteristics of the channels and consequently, the structure and function of the aquatic biota. Although we advise the non-intervention of the lotic systems, we propose some recommendations under an intervention scenario, such as conducting research addressing different facets of biodiversity, publication of results in refereed journals, public access to data, among others. We concluded if the economic benefit derived from coal mining prevails over the aquatic environments preservation there will be a loss of functions and ecological services that are indispensable for the human well-being and the ecosystem balance.
Modification of lotic environments for open pit coal extraction: Effects on biota and recommendations
Keywords: Channel intervention; Coal mining; Ichthyofauna; Open-cut mining; Tropical dry forest